Can Redesign SOP Oriented Time Standardization and Authorization According to Job Description to Waiting Time be a Solution? - Rosita Arviana Masruroh; Achmad Zani Pitoyo; Bramantya Surya Pratama (Universitas Muhammadiyah Yogyakarta, 2022)
Pharmacy installation is part of the service system that influences hospital quality standards, one of which is waiting time for pharmaceutical service. The waiting time at the Outpatient Pharmacy Installation of Hospital X exceeds the Hospital Minimum Service Standard and Hospital Quality Indicators, which is 50 minutes. This study aims to determine the root of the problem and the solution to the long waiting time for prescription drug services at Outpatient Pharmacy installations. This research is a case study with a search method for identifying the root of the problem, determining alternative solutions, and prioritizing the main solution. The long waiting time for finished drug services is caused by the lack of shifts of workers when poly peak times, the absence of flow information and appropriate SOPs when pharmaceutical prescription services run concurrently, and non-compliance by pharmacists with SOPs for pharmaceutical services. The main solution was to create flow information and a new SOP for outpatient prescription services.